A linguagem dos reality TV shows norte-americanos: análise e classificação - Araújo, Rafael Fonseca de (2017)
This thesis presents a Multi-dimensional (MD) analysis (Biber, 1988 et seq.) of a Corpus of American Reality TV Shows (CARTS). Reality television can be described as unscripted television shows with non-professional actors being observed by cameras in preconfigured environments (Kavka, 2012) and despite of being a relatively new TV genre is a cornerstone of contemporary US television programming, since according to some critics it has remade television culture (Murray and Quellette 2004). The major goal of the study was to provide a lexical-grammatical description of the verbal language of Reality TV shows by investigating a corpus of 780 texts taken from 39 popular American Reality TV shows, totaling over 6 million tokens. The specific goals were to compare CARTS against the four dimensions of general English register variation as well as against the five dimensions of American television register variation (Berber Sardinha;; Veirano Pinto, in press). CARTS texts were classified into four main program types (Competition, Documentary, Talent and Professional, and Transformation) and into 13 sub-program types, namely, celebrities, dating, gamedoc, docusoap, hidden cameras, reality sitcoms, business, cooking, fashion, performing, expert guidance, self-improvement and social experimental. The corpus was balanced so that each major category had the same number of texts. CARTS was tagged for part of speech with the Biber Tagger and analyzed by the Bibber Tag Count which calculated the normalized frequencies of the 128 linguistics features considered in the research. The results present the additive MD analysis by showing how reality TV shows are similar or different from others spoken and written English registers (from Biber seminal 1988 study), as well as how the various manifestations of Reality TV compare to television registers on US. Since there is no precedent for studies within Corpus Linguistics dedicated to researching the lexical-grammatical profile of Reality TV Shows in a multidimensional perspective, this research intends to fill this gap